PENGARUH FATWA KEHARAMAN BUNGA BANK TERHADAP KEPUTUSAN BELI PRODUK BANK SYARIAH - ZUBAIR, KAMAL (P3M STAIN Parepare, 2014)
In this time, fast growth of Islamic banking industry progressively is offce network side as consequence of improvement of requirement of society and enthusiasm of bank to provide service. This paper aims to know the perception of civil servants in STAIN Pare-Pare on the prohibition bank interest and to determine the effect of the perception of civil servants in the STAIN Pare-Pare on the decision to use the services of Islamic banks products. Civil servants in STAIN Pare-Pare already understand what it is about Islamic banking, in particular to understand the prohibition of bank interest. Thus, the MUI fatwa on prohibition of bank interest will not be much to change the perception of the civil servants and even the existence of Islamic banks does not affect the decision to use the services of Islamic banks.